Export-promoting policies, agglomeration, and growth - Wataru Johdo (Economic Themes, 2025)
This paper examines the impact of trade subsidies on global growth and national welfare through the cross-border movement of firms in an endogenous growth model. In particular, our model focuses on two key aspects: the cross-border movement of firms and the reallocation of labor resources between the production and innovation sectors. In this paper, we show that, in the presence of local knowledge spillovers, an increase in the trade subsidy by the country where firms are agglomerated leads to an increase in the global growth rate under certain parameter conditions, while an increase in the trade subsidy by the country that is not agglomerated results in a decrease in the global growth rate. Moreover, the results of the welfare analysis show that trade subsidies in the agglomeration country enhance the welfare of both the agglomeration and the non-agglomeration countries, whereas trade subsidies in non-agglomeration country diminish the welfare of both countries.
Keywords: F13; F43; O41; 330; Trade Subsidies; Agglomeration; Global Growth; Local Knowledge Spillover